Effect of exercise on cognitive function and synaptic plasticity in Alzheimer's disease models: A systematic review and meta-analysis - Guo, Linlin; Yang, Xinxin; Zhang, Yuanyuan; Xu, Xinyi; Li, Yan (Frontiers in Aging Neuroscience, 2023)
Introduction Cognitive decline is a central manifestation of Alzheimer's disease (AD), and its process is inseparable from changes in synaptic plasticity. The aim of this review was to summarize and evaluate the effectiveness of exercise on cognitive function and synaptic plasticity in AD animal models. Materials and methods Eligible studies were searched from PubMed, MEDLINE, EMBASE, Web of Science, and Cochrane Library from April to May 2022. The risk of bias was evaluated by Systematic Review Centre for Laboratory Animal Experimentation (SYRCLE). The Morris water maze (MWM) test and synaptic plasticity were considered outcome measures. Data were analyzed using random-effects meta-analyses using the software Stata. Heterogeneity was examined by using I2 test. Sensitivity analysis and publication bias were also assessed. Results A total of 20 randomized controlled studies were eligible for study inclusion. Compared with controls, exercise decreased escape latency (SMD = −0.86, 95% CI: −1.21 to −0.50, P < 0.001), increased platform crossover numbers (SMD = 1.34, 95% CI: 0.57–2.11, P = 0.001) and time in the target quadrant (SMD = 1.65, 95% CI: 0.95–2.36, P < 0.001) and the expression of PSD95 (SMD = 0.73, 95% CI: 0.25–1.21, P = 0.003) in AD animals. The results of the subgroup analysis showed that exercise before AD had a greater effect on escape latency (SMD = −0.88, 95% CI: −1.25 to −0.52, P < 0.001), platform crossover numbers (SMD = 1.71, 95% CI: 1.23–2.18, P < 0.001), time in the target quadrant (SMD = 2.03, 95% CI: 1.19–2.87, P < 0.001) and the expression of PSD95 (SMD = 0.94, 95% CI: 0.19–1.69, P = 0.014) than exercise after AD. The results of the subgroup analysis also showed that treadmill running might be an appropriate exercise type. Conclusion Our findings suggested that exercise had a potential effect on improving cognitive function and synaptic plasticity. It can play a better neuroprotective role before AD. Systematic review registration PROSPERO, identifier: CRD42022328438.